Notice of Armorial Bearings and Inscriptions in the Church of Mid-Calder (Proceedings of the Society of Antiquaries of Scotland, 1862)
This paper discusses the artwork belonging to Sir James Sandiland, Lord Torphichen, that is found in Mid Calder church. The author begins by providing a history of the Sandiland family, as well as a short biography of Sir James himself, who was a notable figure in the Reformation. The article then proceeds to describe the location and appearance of various carved decorations within Mid Calder church.